2019
DOI: 10.2106/jbjs.rvw.18.00042
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Imaging Modalities Assessing Fatty Infiltration in Rotator Cuff Tears

Abstract: Background: Fatty atrophy is a diagnosis characterized by the combination of fatty infiltration and muscle atrophy of the rotator cuff. Studies have shown a strong positive correlation between the level of fatty infiltration and the risk of experiencing a chronic rotator cuff tear. Therefore, the purpose of the present study was to review the current literature on radiographic imaging of fatty infiltration and fatty atrophy to better aid surgeons in predicting functional outcome and to help guide patient decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Functional results may also be theoretically altered by fatty infiltration of the biceps muscle and restoration of postoperative muscle strength, which is also reflective of the time from injury to surgery, as has been demonstrated in other chronic tendon tears including those of the rotator cuff. 12 , 31 , 34 We had hypothesized that functional results would deteriorate and that complication rates would increase as a function of time between tendon injury and surgical reconstruction. In addition to the above-mentioned factors, this was also based on studies by Bisson et al 1 and Kelly et al, 16 which revealed an increased incidence, although not significant, in complication rates as the time between tendon injury and surgical repair increased.…”
Section: Discussionmentioning
confidence: 99%
“…Functional results may also be theoretically altered by fatty infiltration of the biceps muscle and restoration of postoperative muscle strength, which is also reflective of the time from injury to surgery, as has been demonstrated in other chronic tendon tears including those of the rotator cuff. 12 , 31 , 34 We had hypothesized that functional results would deteriorate and that complication rates would increase as a function of time between tendon injury and surgical reconstruction. In addition to the above-mentioned factors, this was also based on studies by Bisson et al 1 and Kelly et al, 16 which revealed an increased incidence, although not significant, in complication rates as the time between tendon injury and surgical repair increased.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have demonstrated the high diagnostic value of high-frequency US, approaching comparability with MRI [ 14 ], US cannot match the precision of MRI in delineating individual muscle bulk loss. However, it can effectively identify and report on fatty replacement and overall atrophy of rotator cuff muscles, particularly when incorporating extended field of view (FOV) techniques [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…Tenbrunsel et al asserted that MRI remains the gold standard for rotator cuff tear imaging and is a superior predictor of clinical outcomes. While US plays a role in reducing healthcare costs, its precision is somewhat compromised due to inherent limitations in comparison to MRI [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
“… 50 , 79 , 87 In 2005, Strobel et al evaluated muscle pennate architecture and echogenicity of the supraspinatus (SSP) and infraspinatus (IS) using US and developed a three-point scale which has been used by other groups to confirm comparable US results to standard magnetic resonance imaging (MRI). 33 , 46 64 , 66 , 68 , 72 , 78 , 84 Despite promising results, drawbacks of US include the inability to distinguish moderate from severe fatty infiltration, problems with US wave penetrance in deep tissue and obese patients, and dependence on operator expertise. 33 , 39 , 67 …”
Section: Diagnosing Fatty Degenerationmentioning
confidence: 99%
“… 16 , 25 Fuchs et al proposed a simplified 3-grade scale whose reliability compared to the traditional Goutallier scheme has been extensively studied and shown to be largely comparable but not necessarily better ( Table I ). 7 , 16 , 30 , 59 , 60 , 63 , 75 , 77 , 78 , 84 , 88 Additionally, radiographical rotator cuff atrophy signs such as the occupation ratio (SSP muscle surface area/SSP fossa surface area) and tangent sign (SSP does not intersect the line from the coracoid’s superior aspect to the superior border of the scapular spine on sagittal MRI) have been shown to correlate strongly with FDRC and may provide quick indications of muscle quality. 37 , 69 , 81 , 88 …”
Section: Diagnosing Fatty Degenerationmentioning
confidence: 99%